INVESTIGATING THE OPERATIONAL ISSUE AND POTENTIAL DEMAND OF AIRPORT BUS SERVICE AT MINANGKABAU INTERNATIONAL AIRPORT - Yaldi, Gusri (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Minangkabau International Airport (MIA) has been operating for nearly a decade. MIA can be visited by using Airport Bus (APB) services provided by the local government. However, it seems the visitors of MIA tend to choose the private travel modes such as passenger cars and motorcycles rather than the APB. Due to the energy crisis as well as other negative impacts of road traffic, MIA visitors are expected to shift from using private travel modes to more sustainable and greener transport modes like APB. However, this policy must be supported by sufficient information and hence the expected outcome could be achieved. This research is aimed at investigating the issues that “preventing” MIA visitors in choosing the existing APB service as well as estimating its potential demand. The result suggests that only 19% of the MIA visitors choose the APB as the travel mode. The visitors tend to use other travel modes due to uncertainty in the APB operation represented by unclear time tables and bus stop locations. In addition, a number of respondents were found did not know the APB service. It is estimated the demand could reach 58% of the total visitor if the aforementioned issues could be properly addressed.